2020
DOI: 10.14744/dajpns.2020.00075
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between quality of life, depression and anxiety in type 1 and type 2 diabetes

Abstract: Objective: Physical, cognitive and emotional changes in diabetic patients affect the treatment process and quality of life. The aim of this study was to investigate the relationship between depression and anxiety symptoms and quality of life in diabetic patients and the differences of these variables with regard to some sociodemographic factors and the type of diabetes. Method:The study sample consisted of 202 patients with diabetes mellitus (83 type 1, 119 type 2 diabetes) admitted to a wellness center in Ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…This result is consistent with studies (Mohamed, 2016;Lassoued, 2017;Al-omairi, 2018) that have resulted in a statistically significant relationship between QOL and motivation for achievement among university students in general, and diabetics in particular, as consistent with the study of (Shao et al, 2017) which concluded that family support is a form of social support that brings positive mental and emotional changes in diabetics; strengthens their resoluteness and confidence in managing their health (physical and psychological health); thus contributes to improving their QOL, as its impact reflects on improving their sugar rare in the blood; it is also consistent with the result (Novita & Novitasari, 2017;Mousavi et al, 2017) which indicated a direct relationship between family support and QOL. In addition to the result of the Study (Al-Mohaimeed, 2017), which concluded that anxiety is more common among patients with impaired social support, it is also consistent with a study (Tveten et al, 2017) which indicated a relationship between Physical Activities and QOL as interest in Physical Activities increases QOL and is also consistent with studies (Kesici & Çavuş, 2019;Martins et al, 2018;Markosyan & Perikhanyan, 2019) which noted that regular physical activity helps in the management of chronic diseases including diabetes, and can improve mental health, QOL and well-being, and to increase interest in university students with type 1 diabetes, the search for variables that can have a positive correlation with their QOL is critical to improving their QOL, because as previous studies have indicated that they suffer from some psychological and physical problems, which may negatively affect their QOL (Cakmak & Gen , 2020;Delevatti et al, 2018;Jawadi. and Turki, 2018;Molvaer et al, 2020;Raymakers et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This result is consistent with studies (Mohamed, 2016;Lassoued, 2017;Al-omairi, 2018) that have resulted in a statistically significant relationship between QOL and motivation for achievement among university students in general, and diabetics in particular, as consistent with the study of (Shao et al, 2017) which concluded that family support is a form of social support that brings positive mental and emotional changes in diabetics; strengthens their resoluteness and confidence in managing their health (physical and psychological health); thus contributes to improving their QOL, as its impact reflects on improving their sugar rare in the blood; it is also consistent with the result (Novita & Novitasari, 2017;Mousavi et al, 2017) which indicated a direct relationship between family support and QOL. In addition to the result of the Study (Al-Mohaimeed, 2017), which concluded that anxiety is more common among patients with impaired social support, it is also consistent with a study (Tveten et al, 2017) which indicated a relationship between Physical Activities and QOL as interest in Physical Activities increases QOL and is also consistent with studies (Kesici & Çavuş, 2019;Martins et al, 2018;Markosyan & Perikhanyan, 2019) which noted that regular physical activity helps in the management of chronic diseases including diabetes, and can improve mental health, QOL and well-being, and to increase interest in university students with type 1 diabetes, the search for variables that can have a positive correlation with their QOL is critical to improving their QOL, because as previous studies have indicated that they suffer from some psychological and physical problems, which may negatively affect their QOL (Cakmak & Gen , 2020;Delevatti et al, 2018;Jawadi. and Turki, 2018;Molvaer et al, 2020;Raymakers et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…In the face of the increasing number of people with diabetes in Saudi Arabia, doctors have been informed to conduct studies on the physiology of the disease, but within the limits of the researchers' knowledge studies related to the physiology of the disease with other variables such as QOL, as people with this disease have a special view of life they live, where the study of (Cakmak & Gen, 2020) indicated that the incidence of diabetes has an impact on QOL, where it is considered an independent factor for the quality of social life, so QOL can be predicted through it. The perception of diabetics towards themselves, and the society in which they live is different when compared to the healthy ones, where they suffer from psychological stress, face psychological and social difficulties, and the support provided to them is QOL sought by each infected person (Jawadi and Turki, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have reported that anxiety and depression are independent predictors of poor quality of life (22,23). In our study, significant relationships were found between quality of life and anxiety and depression.…”
Section: Discussionsupporting
confidence: 67%
“…These poor health behaviours are strongly associated with decreased life expectancy. Additionally, they appeared to be at a higher risk for medical problems such as obesity, diabetes type 2, hypertension, and musculoskeletal disorder (28,29). Sleeping is also one of the important terms that need to be given attention as people who are not satisfied with their sleeping patterns, have less duration of sleep time and reduce sleeping efficiency, are at greater risk to have depression (30).…”
Section: Self-rated Health and Depressionmentioning
confidence: 99%